The Influence of Sugar Consumption and International Sugar Prices toward the Volume of Sugar Import in Indonesia - Sakila Eta Agustin; Sugiyanta - Sugiyanta; Rusmini - Rusmini (JOBS (Jurnal Of Business Studies), 2021)
This study examines the effect of Sugar Consumption and International Sugar Prices on the volume of Sugar Imports in Indonesia. This study uses secondary data from 2010 to 2019 obtained from the Central Bureau of Statistics, the Ministry of Agriculture, and the World Bank. To be able to solve the problem using multiple linear regression analysis techniques, F test for simultaneous influence and t-test for partial effect. The t-test result shows that the sugar consumption partially has no significant effect, while the international sugar price partially has a significant effect on the volume of Indonesia’s sugar import. Simultaneously sugar consumption and international sugar prices have a significant effect of 52,6% toward the volume of Indonesia’s sugar import and the rest of 47,4% are from other variables.